Kolaborasi Model Fun-N-Pick dan Team Game Tournament dalam Meningkatkan Self Esteem: Fun-N-Pick Model Collaboration and Team Game Tournament to Improve Self Esteem - Hakim, Arief Rahman; Soetjipto, Budi Eko; Hanurawan, Fattah (Universitas Muhammadiyah Sidoarjo, 2017)
One effort to increase self-esteem (self esteem) students in school is through the optimization of cooperative learning with models collaborate fun-n-pick and team game tournament. Where both models support each other, but remain separate and not become a new model. The purpose of this study was to explain whether the implementation of cooperative learning collaborative model of Fun-n-pick and team games tournament can meningkatkatkan esteem (self esteem) in Class VI SDN Putat Kidul 01 District Gondanglegi and describe the obstacles faced and the support it receives in implementing collaboration models fun-n-pick and team game tournament. Through action research by using two cycles of research and sixth grade students of Putat Kidul 01 Elementary School District Gondanglegi by the number of students 30 people as the subject. The tools used to collect data in the form of documentation and questionnaires. Sources of data obtained directly from students by actions in the classroom. The results showed that the implementation of cooperative learning collaborative model of Fun-N-Pick and team games tournament can meningkatkatkan esteem (self esteem) students in the school, and outline the obstacles in this study is found in the first cycle, but these barriers can be overcome and make an endorsement in implementing collaborative model of fun-n-pick and team game tournament.